(125)I Brachytherapy Seeds Implantation for Inoperable Low-Grade Leiomyosarcoma of Inferior Vena Cava - Li, Yuliang (The Korean Society of Radiology, 2013)
A 60-year-old female presented with abdominal pain and tenderness of five-day duration. Contrast enhanced CT showed a mass of 9 × 6 × 5.5 cm in size with almost complete obliteration of the inferior vena cava and massive extension to the extravascular space. CT-guided biopsy demonstrated a low-grade leiomyosarcoma. The patient underwent (125)Iodine seeds implantation in two sessions, and another balloon cavoplasty. Abdominal pain and tenderness gradually improved and the patient continues to remain as disease free state for three years after the procedures.